2021
DOI: 10.1186/s11671-020-03470-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced UV Emission from ZnO on Silver Nanoparticle Arrays by the Surface Plasmon Resonance Effect

Abstract: Periodical silver nanoparticle (NP) arrays were fabricated by magnetron sputtering method with anodic aluminum oxide templates to enhance the UV light emission from ZnO by the surface plasmon resonance effect. Theoretical simulations indicated that the surface plasmon resonance wavelength depended on the diameter and space of Ag NP arrays. By introducing Ag NP arrays with the diameter of 40 nm and space of 100 nm, the photoluminescence intensity of the near band-edge emission from ZnO was twofold enhanced. Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…To enhance the light emission of sample A, Ag/SiO 2 NPs were embedded on the surface of aligned nanorod LEDs via the LSP coupling effect. It is well-known that the LSP resonance depends on the shape, size, and density of Ag/SiO 2 NPs that control the strength and spatial orientation of the electromagnetic LSP field. Ahead of these factors, energy matching between the emission wavelength of a nanorod LED and the Ag NPs is a crucial factor. Therefore, the spherical Ag/SiO 2 NPs were prepared to accomplish energy matching with the blue-emitting InGaN/GaN nanorod LEDs.…”
Section: Resultsmentioning
confidence: 99%
“…To enhance the light emission of sample A, Ag/SiO 2 NPs were embedded on the surface of aligned nanorod LEDs via the LSP coupling effect. It is well-known that the LSP resonance depends on the shape, size, and density of Ag/SiO 2 NPs that control the strength and spatial orientation of the electromagnetic LSP field. Ahead of these factors, energy matching between the emission wavelength of a nanorod LED and the Ag NPs is a crucial factor. Therefore, the spherical Ag/SiO 2 NPs were prepared to accomplish energy matching with the blue-emitting InGaN/GaN nanorod LEDs.…”
Section: Resultsmentioning
confidence: 99%
“…For a certain size and particle density, absorption may become dominant over scattering leading to PL quenching. ,, Usually, the larger metallic NPs provide a larger scattering cross section in coupling surface plasmons to light to increased UV emission, whereas in the smaller ones, absorption dominates over the scattering . Distance/space between the metallic NPs was also found to be an important aspect of the PL enhancement process. , Different plasmonic modes can be activated in a system depending on the distance between metallic nanoparticles . Collective modes predominate when particles interact with each other, which happens when the distance between them is sufficiently small.…”
Section: Resultsmentioning
confidence: 99%
“…16 Distance/space between the metallic NPs was also found to be an important aspect of the PL enhancement process. 16,54 Different plasmonic modes can be activated in a system depending on the distance between metallic nanoparticles. 55 Collective modes predominate when particles interact with each other, which happens when the distance between them is sufficiently small.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Wei et al reported a one-dimensional microbelt/Au-nanoparticles construction to enhance the nonlinear third harmonic emission via the LSP effect [ 26 ]. Wang et al reported enhanced UV emission from ZnO on Ag NP arrays by the LSP effect [ 27 ]. To date, the enhancement of high-order multiphoton upconversion UV lasers by localized surface plasmon resonance effect has been rarely reported and requires in-depth analysis.…”
Section: Resultsmentioning
confidence: 99%